Digital Technology Scale to Coach People with Chronic Diseases: Evidence of Psychometric Validity in Four European Countries - Ferreira, Paulo Alexandre Carvalho (2021)
Noncommunicable diseases (NCDs) bring new challenges for the healthcare sector, demanding a paradigm shift on healthcare deliverance. In this sense, information and communication technologies (ICTs) are being more and more used, implying a change in educational programs of nursing schools. The application of ICTs in healthcare is often linked with concepts like 'patient engagement' or 'patient empowerment', implying an active participation of the patient in the therapeutic process. Although coaching in a context where NCDs are present is well studies, nursing curricula seems to lack consistent content for future nurses. This study aims to develop a tool to explore nursing student's perceived easiness of use and perceived utility of potential ICTs in the coaching of people with chronic diseases. The scale's items list (n = 45) emerged from a recent study published in the nursing students' digital competencies area. The scale was developed based on the Technology Acceptance Model (TAM) and other conceptual models. The scale was reviewed and discussed by a panel of experts and then translated into four languages (Portuguese, Slovenian, Flemish, and Finnish). The scale was applied to undergraduate nursing students from five universities from Portugal, Finland, Belgium and Slovenia. A total of 874 students were enrolled, with a mean age of 22.38 years (SD = 5.49), being 621 (71.1%) females. The most significant dimensions were Professional Performance, Relationship and Patient Empowerment. DTS-NCD constitutes a good tool to explore nursing student's perceptions relating the use of ICTs.